A comprehensive set of criteria for assessing housing affordability - Tytok, V (Ways to Improve Construction Efficiency, 2019)
The concept of affordable housing is a controversial issue, but an urgent and widespread problem in many countries. Housing affordability is a complex multifaceted indicator that not only reflects the course of market reforms in the housing sector, their social orientation, but is also related to the overall flow of socio-economic processes in society, their success, takes into account the behavior of the population in the housing market, its expectations, degree of trust in government and commercial institutions. The opportunity to improve living conditions is a complex category in which the demographic, socio-economic characteristics of the current level of well-being of the population, the parameters of the budget-regulatory and credit-financial system, the price and tariff policy in the field of housing and housing and communal services are closely intertwined. Speaking about the affordability of housing, it is necessary to consider not only the possibility of its free purchase for further accommodation. At the same time as the purchase, there is a need to maintain and maintain this home, bearing the appropriate costs, which include tax deductions, overhaul, various types of insurance, utility bills and some others. The study is based on the view that the problem of housing affordability covers more than the financial cost of housing and the ability of households to cover such costs, and should address larger problems such as social and environmental sustainability and household well-being. The neighborhood should have good transport links, public parks, recreation and sports facilities, low crime rates, job and study opportunities, educational institutions, health and social care facilities, kindergartens, as well as a wide range of public, voluntary and private institutions .. Therefore, there is a need for a broad and comprehensive set of criteria to assess the affordability of housing. The article presents a system of criteria by which you can comprehensively and continuously evaluate the availability of different places of residence.